2013 IEEE International Conference on Systems, Man, and Cybernetics 2013
DOI: 10.1109/smc.2013.435
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricle Segmentation by Temporal Information Constrained Gradient Vector Flow

Abstract: Evaluation of right ventricular (RV) structure and function is of importance in the management of most cardiac disorders. But the segmentation of RV has always been considered challenging due to low contrast of the myocardium with surrounding and high shape variability of the RV. In this paper, we present a 2D + T active contour model for segmentation and tracking of RV endocardium on cardiac magnetic resonance (MR) images. To take into account the temporal information between adjacent frames, we propose to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Integrating time-dependent constraints into the energy function of the classical GVF, Yang et al proposed a 2D+t AC model [27]. Based on the "dt" model defined in Equation (10), the temporal information for a frame at time t was defined between adjacent frames; "the previous K frames at time t − i, the next K frames at time t + i, where K is an integer parameter denoting the time offset between the frames".…”
Section: Deformable Methodsmentioning
confidence: 99%
“…Integrating time-dependent constraints into the energy function of the classical GVF, Yang et al proposed a 2D+t AC model [27]. Based on the "dt" model defined in Equation (10), the temporal information for a frame at time t was defined between adjacent frames; "the previous K frames at time t − i, the next K frames at time t + i, where K is an integer parameter denoting the time offset between the frames".…”
Section: Deformable Methodsmentioning
confidence: 99%
“…A number of researchers have chosen to use traditional segmentation algorithms. Deformable models are widely used [4], [5], [6], [7] due to their efficient detection of boundaries and variation in shape or complex geometry. Arrieta et al suggested a TPLS technique based on the saved structure level sets using a restricted base of 35 pathological patients and 6 healthy cases.…”
Section: State Of the Artmentioning
confidence: 99%
“…Since atlas-based methods depend at the first stage on the database used, its results may fail to provide high accuracy when the segmented cardiac images present different structures from those used in the first place. Deformable models are also used for RV segmentation such in [9] and [10]. These methods are based on the shape information of the right ventricular.…”
Section: State Of the Artmentioning
confidence: 99%